2023
DOI: 10.1177/02841851231177394
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of high-frequency ultrasound for Poland syndrome

Abstract: Background The imaging diagnosis of Poland syndrome is mostly computed tomography (CT) or magnetic resonance imaging (MRI), whereas high-frequency ultrasound for the diagnosis of Poland syndrome is relatively rare. Purpose To investigate the diagnostic value of high-frequency ultrasound for Poland syndrome. Material and Methods A retrospective analysis of 15 patients diagnosed with Poland syndrome was performed, and the characteristics of ultrasound images were summarized. Results High-frequency ultrasound cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As a consequence, it is suggested that an abnormality in the vasculature formation may be the main cause of this sequence [ 4 , 9 - 10 ]. Although it is not easy to detect Poland Syndrome prenatally by ultrasound monitoring, some of its most common anatomical abnormalities (widening of coronal sutures, absence of the ossification of cranial and pubic bones, absence/hypoplasia of nasal bone, and hypoplasia of the thoracic cage) found in affected foetuses may be detected prenatally by ultrasound scan [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it is suggested that an abnormality in the vasculature formation may be the main cause of this sequence [ 4 , 9 - 10 ]. Although it is not easy to detect Poland Syndrome prenatally by ultrasound monitoring, some of its most common anatomical abnormalities (widening of coronal sutures, absence of the ossification of cranial and pubic bones, absence/hypoplasia of nasal bone, and hypoplasia of the thoracic cage) found in affected foetuses may be detected prenatally by ultrasound scan [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome can also be concurrent with conditions like scoliosis or diaphragmatic hernia. Scoliosis in PS is often attributed to muscular imbalances in the shoulder girdle [ 5 ]. Additionally, the co-occurrence of congenital diaphragmatic hernia and PS is thought to be more than coincidental, possibly sharing a common developmental origin or laterality defect [ 6 ].…”
Section: Discussionmentioning
confidence: 99%